Ultra Vires Perlindungan Hukum Terhadap Kreditur Dalam Perseroan Terbatas - Rafiqa Sari; Winanda Kusuma; A. Cery Kurnia (PROGRESIF: Jurnal Hukum, 2019)
The Board of Directors in carrying out the management of the company is subject to the principles of civil law. If the Board of Directors deviates from the principle, it is called conducting Ultra Vires. This action can certainly have positive and negative consequences for shareholders both majority and minority can test at the General Meeting of Shareholders. The ultra vires action by the directors is detrimental to the creditor, the legal mechanism that needs to be studied in more depth to get the answer. This study aims to analyze the legal protection of creditors for directors of limited companies conducting Ultra Vires and analyze legal remedies against restoring the creditor's rights to directors of limited companies conducting Ultra Vires. (1) Does the law regulate the protection of creditors for directors of limited companies conducting Ultra Vires ?; (2) How does the law restore creditor rights over the directors of the limited company to conduct Ultra Vires ?. With these legal issues, the basis for protecting third parties. These principles include the Goodwill Principle, the Pacta Sunt Servanda Principle and the Modern Ultra Vires Doctrine. By relying on these fundamentals, preventive legal protection and repressive legal protection can be given. Legal remedies for recovery are based on the first, actions containing aspects of repairing and preventing, and secondly, actions or efforts containing aspects aimed at recovering, including ratification and compensation.